O ensino de ciências da natureza sob o enfoque do tema horta escolar e compostagem - Pires, Keine Cristina (2021)
This research is based on the elaboration and development of an interdisciplinary Didactic Sequence (DS) on the theme Vegetable Garden and Composting. The activities are guided by the ethical, political and aesthetic principles of human and integral formation, also present in the Brazilian National Common Curricular Base (BNCC). The investigation was motivated by the ideas of different authors that shared thoughts, reflections and theoretical assumptions, such as: the universalization of interdisciplinary knowledge, proposed by Magalhães (2005); learning through life projects, meaning, emotion and reason, proposed by Freire (2005),Freire’s contributions in favor of Environmental Education, relating to the conceptions of being human, of the world and of Education and learning and education characterized of an interactive, continuous and systematized process, supported by Vygotsky. The curricular and methodological proposal was developed throughout the academic year of 2019, targeting Basic Education students from a public school in Uberlândia, Minas Gerais, Brazil. The proposal was monitored with the registries of interdisciplinary activities and diaries of pedagogical practices. It was contemplated practices that conceived knowledge in a qualitative, interdisciplinary, contextualized, interactive and dialogic. Data was collected based on the generator theme Vegetable Garden and Composting. The didactic sequence was defined as the educational product of the presented research. Being the same,divided into stages. A virtual diary (final stage of the DS) of educational record was explored via the construction of a blog by the students and mediated by the teacher, which was fed as the practices related to the theme were presented. Thus, digital information and communication technologies were explored in a critical, meaningful, reflexive and ethical manner, also enabling communication, through different languages and media (BNCC). In parallel with the work developed at the School Garden, the students used the technique of Composting by recycling organic matter in order to make fertilizer to use in the school vegetable garden. The subject in question, Vegetable Garden and Composting provided, in addition to the experiences of awareness, contextualization and meaning a real contact with biotic and abiotic factors as well as familiarity with the virtual environment, web and technological world.